The influence of maximal strength performance of upper and lower extremities and trunk muscles on different sprint swim performances in adolescent swimmers - Keiner, M.; Yaghobi, D.; Sander, A.; Wirth, K.; Hartmann, H. (Science & Sports, 2015)
Objectives: Strength and speed are 2 major factors that determine a swimmer's sprint performance, especially swim sprint performance and swim starts. This study identified and examined variables that determine the influence of maximal strength performance on different swim performance styles and distances in trained adolescent swimmers. Equipment and methods: Twenty-one regional swimmers (12 males and 9 females, 17.5 ± 2 years; mass: 69.5 ± 11.4 kg; height: 177.3 ± 10.1 cm) volunteered to take part in the present study. One-repetition-maximum (1RM) in the back squat, dead lift, bent-over row and sit-up were used to determine maximum strength. Squat jump (SJ) and countermovement jump (CMJ) were evaluated to determine speed-strength performance. Swim performances of 15 to 100 meters in freestyle, breaststroke and backstroke were measured in a 25-m indoor pool. Pearson correlation analysis was used to assess the relationships between strength and power variables and swim variables. Results: Strong negative correlations between leg strength (1RM squat), speed-strength (SJ and CMJ) and swim performance were found in this investigation, especially for short distances (up to 25 m, r = -0.75 to -0.94, P < 0.05). Additionally, moderate to mostly strong correlations (r = -0.37 to -0.85, P < 0.05) were found between the strength tests of the upper extremities, and non-uniform correlations were found for the trunk strength test (r = -0.05 to -0.68) and swim performance. Conclusion: The maximal strength parameters of the upper and lower extremities and maximal trunk strength are good predictors of performance in sprint swimming in trained adolescent swimmers in different disciplines.